DESCRIPTION OF FACTORS RELATED TO SEVERITY OF DIABETIC MELLITUS PATIENT TYPE 2 (Study in RSUD Kota Semarang) - Dwi Hardianti; M. Sakundarno Adi; Lintang Dian Saraswati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Diabetic ulcer is a chronic complication of diabetes mellitus. It is an open wound on the skin surface which is accompanied by a death tissue on the area. The prevalence of diabetic ulcer in RSUD Semarang had increased by 0,36% from 2013 to 2014. The purpose of this study were to describe the factors associated with the severity of diabetic ulcer in patients with type 2 diabetes mellitus in RSUD Semarang. This research was descriptive observational with cross sectional design. Samples of this research were 100 patients of diabetic ulcer using consecutive sampling method. The questionnaires filled were Food Frequency Questioner and Nottingham Assesment of Functional Footcare, in addition, medical record was used as secondary data. The study conclued that the majority of severity level was grade 3 (27%), female (55%), aged over 57 years old (53%), had senior high school degree (37%), housewife (37%), suffering from DM more than 6 years (54%), had high glucose level (52%), non-hypertensive (73%), non-smoker (69%), previously suffering from ulcer (91%), non-obese (71%), doing foot treatment regularly (58%), not wearing appropriate footwear (55%), and not obeying the diet (51%). The suggestion is that diabetic ulcer patient should obey the diet since it is found from the research that the respondents who suffering from hypertension, obesity, and not obeying the diet are the majority in grade 5.